Efficient and scalable gene delivery method with easily generated cationic carbon dots. - Algarra-González, Manuel; González-Muñoz, María Elena (BMC, 2024)
Gene delivery is a complex process with several challenges when attempting to incorporate genetic material efficiently and safely into target cells. Some of the key challenges include not only efficient cellular uptake and endosomal escape to ensure that the genetic material can exert its effect but also minimizing the toxicity of the delivery system, which is vital for safe gene delivery. Of importance, if gene delivery systems are intended for biomedical applications or clinical use, they must be scalable and easy and affordable to manufacture to meet the demand. Here, we show an efficient gene delivery method using a combination of carbon dots coated by PEI through electrostatic binding to easily generate cationic carbon dots. We show a biofunctional approach to generate optimal cationic carbon dots (CCDs) that can be scaled up to meet specific transfection demands. CCDs improve cell viability and increase transfection efficiency four times over the standard of PEI polyplexes. Generated CCDs enabled the challenging transfection protocol to produce retroviral vectors via cell cotransfection of three different plasmids into packing cells, showing not only high efficiency but also functionality of the gene delivery, tested as the capacity to produce infective retroviral particles.
Keywords: Polímeros; Ingeniería genética; Transfección; Transducción; Transformación genética; Carbon dots; Polyethyleneimine (PEI); Cell transfection; Gene delivery; Cell transduction